Genetic improvement of some microorganisms to increase the effect of bio-control on the potato tuber moth, Phthorimaea operculella (Zeller) (Lepidoptera: Gelechiidae) - Shereen Abdel-Hameed Mohamed; Abd-El-Aal S. Kh; S. S. Moawad; A. G. Attallah (Egyptian Journal of Biological Pest Control, 2023)
Abstract Background During the last five decades, chemical synthetic pesticides have been used extensively to control pests and protect crops. Use of synthetic pesticide has caused some unfortunate consequences like environmental pollution, pest resistance and toxicity to other non-target organisms. Due to the hazardous effects of their chemical residues to human and animal health, several studies have been carried out to determine effective alternative control methods. One of methods is the usage of entomopathogens such as bacteria, virus and fungi. Entomopathogenic bacteria have unique insecticidal properties mainly due to the production of larvicidal proteins that accumulate as parasporal crystalline inclusions within the cell. The bio-insecticidal bacterium Bacillus thuringiensis (Bt) has been widely used in agriculture for the control of pest insects which attack crops. Results Thirteen genetically stable fusants strains were obtained as a result of protoplast fusion technique between a local Bacillus thuringiensis (Bt) and each of B. subtilis subsp. subtilis strain (Bs1), Bacillus licheniformis strain (Bl) or B. subtilis subsp. spizizeniie (Bs2). Thirteen fusants were obtained, including three fusants (group B) from Bt::Bs1 fusion, six fusants (group C) from Bt::Bl fusion and four fusants (group D) from Bt::Bs2 fusion. All fusants were chosen for bioassay treatments against the potato tuber moth (PTM) Phthorimaea operculella (Zeller) (Lepidoptera: Gelechiidae) which recorded a high mortality percentage of PTM ranged from 75 to 80% in F1 and F2 of first attempt B (Bt::Bs1). The accumulative larval mortality was notation the highest percentage reached to 90% in case of treatment by fusants F4 followed by F7, F8 and F9 which gave 75, 70 and 80% larval mortality, respectively, for second attempt C (Bt::Bl). The third attempt D (Bt::Bs2) fusants F10, F11, F13 achieved the highest mortality percentage up to 60, 60 and 70%, respectively. Expression of apoptosis-related encoding genes in PTM was determined in three fusants B (Bt::Bs1), C (Bt::Bl) and D (Bt::Bs2) and compared with A (Bt) and Control. The results showed a high expression of gene apoptosis to fusants D (Bt::Bs2) to Caspase-16 gene, Dronc and Dredd genes in tissues of the (PTM) treated with different biological pesticides. Conclusions The study used protoplast fusion technique between a local Bacillus thuringiensis (Bt) and B. subtilis subsp. subtilis strain (Bs1), B. licheniformis strain (Bl) and B. subtilis subsp. spizizeniie (Bs2). Thirteen fusants were chosen for bioassay treatments against PTM. Bacterial fusant, F1, F2, F4, F7, F9 and F13, achieved the highest mortality rates against PTM ranged 75–90% under laboratory conditions. The highest expression of gene apoptosis to fusants D (Bt::Bs2) to Caspase-16 gene, Dronc and Dredd genes was recorded in insect tissues treated with different bio-insecticides. As a result of the effected on the genes responsible for expression the vital processes (genes of apoptosis) in the insect as a result of treatment with bacteria, this led to deformities and death of PTM.